Rapid determination of zinc in foods by flow injection analysis with flame AAS using gradient calibration method - Anzano, Jesús M.; Heinemann, Riana J. B. [UNESP]; Mir, José Ma. (My University, 2004)
A calibration method was developed using flow injection analysis (FI) with a Gradient Calibration Method (GCM). The method allows the rapid determination of zinc In foods (approximately 30 min) after treatment with concentrated sulphuric acid and 30% hydrogen peroxide, and analysis with flame atomic absorption spectrometry (FAAS). The method provides analytical results with a relative standard deviation of about 2% and requires less time than by conventional FI calibration. The electronic selection of different segments along the gradient and monitoring of the technique covers wide concentration ranges while maintaining the inherent high precision of flow injection analysis. Concentrations, flow rates, and flow times of the reagents were optimized in order to obtain best accuracy and precision. Flow rates of 10 mL/min were selected for zinc. In addition, the system enables electronic dilution and calibration where a multipoint curve can be constructed using a single sample injection.
Keywords: hydrogen peroxide; sulfuric acid; zinc; accuracy; analytic method; atomic absorption spectrometry; calibration; flame atomic absorption spectrometry; flow injection analysis; flow rate; food analysis; intermethod comparison